A Linear Free Energy Relationship Treatment of the Affinity between Carboxymethylcellulose and Basic Drugs - Ramírez Rigo, María Veronica (2004)
With the purpose of getting information about the factors that determine the affinity between basic drugs (B) and the acid form of carboxymethylcellulose (HCMC), the constant Kip for the equilibrium HCMC + B a CMC- BH+ was measured using a set of nine model B. A linear free energy relationship (LFER) was developed through a multiple correlation of log Kip against (pKa + log PC), in which the octanol-water partition coefficient (PC) was introduced as an indicator of the hydrophilicity of B. Both magnitudes, pKa and log PC, contribute to a rise in log Kip. In addition, water uptake and drug delivery were assayed with the product of neutralization of HCMC with atenolol, which was easily wetted, and the drug-HCMC interaction was found essentially reversible.